Development of a hybrid light alloy - carbon fibre aerospace structural panel - Roets, Philip J. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.